Disrupted brain network functional dynamics and hyper‐correlation of structural and functional connectome topology in patients with breast cancer prior to treatment. Issue 3 (6th February 2017) - Kesler, Shelli R.; Adams, Marjorie; Packer, Melissa; Rao, Vikram; Henneghan, Ashley M.; Blayney, Douglas W.; Palesh, Oxana
Abstract: Introduction: Several previous studies have demonstrated that cancer chemotherapy is associated with brain injury and cognitive dysfunction. However, evidence suggests that cancer pathogenesis alone may play a role, even in non‐CNS cancers. Methods: Using a multimodal neuroimaging approach, we measured structural and functional connectome topology as well as functional network dynamics in newly diagnosed patients with breast cancer. Our study involved a novel, pretreatment assessment that occurred prior to the initiation of any cancer therapies, including surgery with anesthesia. We enrolled 74 patients with breast cancer age 29–65 and 50 frequency‐matched healthy female controls who underwent anatomic and resting‐state functional MRI as well as cognitive testing. Results: Compared to controls, patients with breast cancer demonstrated significantly lower functional network dynamics ( p  = .046) and cognitive functioning ( p  < .02, corrected). The breast cancer group also showed subtle alterations in structural local clustering and functional local clustering ( p  < .05, uncorrected) as well as significantly increased correlation between structural global clustering and functional global clustering compared to controls ( p  = .03). This hyper‐correlation between structural and functional topologies was significantly associated with cognitive dysfunction ( p  = .005). Conclusions: Our findings could not be accounted for by psychological distress and suggest that non‐CNS cancer may directly and/or indirectly affect the brain via mechanisms such as tumor‐induced neurogenesis, inflammation, and/or vascular changes, for example. Our results also have broader implications concerning the importance of the balance between structural and functional connectome properties as a potential biomarker of general neurologic deficit. Abstract : Cancer pathogenesis is believed to play a role in cancer‐related cognitive dysfunction. We measured brain structure, function, and functional dynamics in newly diagnosed breast cancer patients prior to any cancer treatments. Compared to healthy controls, patients with breast cancer demonstrated reduced functional network dynamics as well as hyper‐correlation of structural connectome clustering and functional connectome clustering.